Smart Desks to Promote Comfort, Health, and Productivity in Offices: A Vision for Future Workplaces - Aryal, Ashrant; Becerik-Gerber, Burcin; Anselmo, Francesco; Roll, Shawn C.; Lucas, Gale M. (Frontiers in Built Environment, 2019)
Abstract: People spend most of their day in buildings, and a large portion of the energy in buildings is used to control the indoor environment for creating acceptable conditions for occupants. However, majority of the building systems are controlled based on a ‘one size fits all’ scheme which cannot account for individual occupant preferences. This leads to discomfort, low satisfaction and negative impacts on occupants’ productivity, health and well-being. In this paper, we describe our vision of how recent advances in Internet of Things (IoT) and machine learning can be used to add intelligence to an office desk to personalize the environment around the user. The smart desk can learn individual user preferences for the indoor environment, personalize the environment based on user preferences, and act as an intelligent support system for improving user comfort, health and productivity. We briefly describe the recent advances made in different domains that can be leveraged to enhance occupant experience in buildings and describe the overall framework for the smart desk. We conclude the paper with a discussion of possible avenues for further research.